2008
DOI: 10.1038/onc.2008.388
|View full text |Cite|
|
Sign up to set email alerts
|

Deacetylation of cortactin by SIRT1 promotes cell migration

Abstract: Cortactin binds F-actin and promotes cell migration. We showed earlier that cortactin is acetylated. Here, we identify SIRT1 (a class III histone deacetylase) as a cortactin deacetylase and p300 as a cortactin acetylase. We show that SIRT1 deacetylates cortactin in vivo and in vitro and that the SIRT1 inhibitor EX-527 increases amounts of acetylated cortactin in ovarian cancer cells. We also show that p300 acetylates cortactin in vivo and that cells lacking or depleted of p300 express lessacetylated cortactin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
171
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(181 citation statements)
references
References 59 publications
(74 reference statements)
7
171
0
Order By: Relevance
“…It has been reported that the cellular role of CTTN is related to membrane dynamics and cortical actin assembly (Lua and Low, 2005 (Kinley et al, 2003). Zhang et al (2009) reported that deacetylation of CTTN promotes cell migration of breast and ovarian cancer. In this study, fluorescently labeled phalloidin staining showed that the assembled F-actin decreased in CRT-siRNA cells as compared with non-silencing siRNA and parental ESCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the cellular role of CTTN is related to membrane dynamics and cortical actin assembly (Lua and Low, 2005 (Kinley et al, 2003). Zhang et al (2009) reported that deacetylation of CTTN promotes cell migration of breast and ovarian cancer. In this study, fluorescently labeled phalloidin staining showed that the assembled F-actin decreased in CRT-siRNA cells as compared with non-silencing siRNA and parental ESCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, Zhang and collaborators identified an F-actin binding protein, cortactin, as a new target for acetylation. Cortactin acetylation is regulated through different factors (PCAF, p300, HDAC6, and SIRT1), leading to the reduction of cortactin binding to F-actin and cell mobility [189,190]. Recently, Cortactin acetylation was also shown to affect dendritic spine morphogenesis, promoting the dendritic clustering of PSD95 and Shank1, two post-synaptic proteins, in excitatory hippocampal synapses.…”
Section: Non-histone Protein Acetylation In Synaptic Plasticity and Mmentioning
confidence: 99%
“…In humans, several types of cancer, including prostate (6,7), breast cancer (8,9), colon (10,11), glioblastoma (12), lymphoma (13) and acute myeloid leukemia (14) have been demonstrated to have a significantly increased expression of SIRT1. Furthermore, a recent study showed that SIRT1 regulates the DNA damage signaling pathway through deacetylation of NBS1 to promote cellular survival (15).…”
Section: Introductionmentioning
confidence: 99%